The development of students’ self-regulated learning through online learning design - El-Rumi, Umiarso (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2022)
This study focused on exploring how the online learning design of Pendidikan Agama Islam (PAI) course facilitated the development of students’ self-regulated learning. This study was conducted at the State University of Malang, Indonesia, and used a qualitative approach in the form of a case study as its research method. Based on Bandura’s learner agency theory, the data were collected through documentation, online-based interviews, and observation. After being collected, the data then were analyzed using the interactive model of Miles, Huberman, and Saldana. Findings show that the PAI course at the State University of Malang had four learning design stages: stimulation and problem identification, learning problem-content analysis, verification of results, and generalization. These stages facilitated the development of students’ self-regulated learning, as observed through three indicators owned by each student, namely, creativity, ability to think critically, and self-regulation. The implication of this study is the emergence of the technical-didactic side of online Islamic education learning through a designed learning design stage so that, in the end, it will lead to benefits in achieving educational goals more effectively.